2017
DOI: 10.1371/journal.pgen.1006957
|View full text |Cite
|
Sign up to set email alerts
|

MYT1L mutations cause intellectual disability and variable obesity by dysregulating gene expression and development of the neuroendocrine hypothalamus

Abstract: Deletions at chromosome 2p25.3 are associated with a syndrome consisting of intellectual disability and obesity. The smallest region of overlap for deletions at 2p25.3 contains PXDN and MYT1L. MYT1L is expressed only within the brain in humans. We hypothesized that single nucleotide variants (SNVs) in MYT1L would cause a phenotype resembling deletion at 2p25.3. To examine this we sought MYT1L SNVs in exome sequencing data from 4, 296 parent-child trios. Further variants were identified through a genematcher-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
99
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 64 publications
(114 citation statements)
references
References 46 publications
4
99
1
Order By: Relevance
“…Only three of the nine individuals developed overweight/obesity postnatally. Thus, the frequency for overweight/obesity among these novel individuals is lower than reported before with 33% as compared to, for example, the 85% reported earlier (Blanchet et al, ). Severe congenital malformations were absent and craniofacial dysmorphism was generally mild.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…Only three of the nine individuals developed overweight/obesity postnatally. Thus, the frequency for overweight/obesity among these novel individuals is lower than reported before with 33% as compared to, for example, the 85% reported earlier (Blanchet et al, ). Severe congenital malformations were absent and craniofacial dysmorphism was generally mild.…”
Section: Discussioncontrasting
confidence: 61%
“…One important example is overweight or obesity which affected all reported individuals with microdeletions affecting MYT1L in the first review, (Stevens et al, ). De Rocker et al found overweight/obesity of childhood onset in 71% of their deletion patients and both of their SNV patients (De Rocker et al, ) and Blanchet and colleagues in 85% of their novel and reviewed patients (Blanchet et al, ). However, only three out of the nine novel individuals presented here were affected.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Chromosome microdeletions frequently cause disease through haploinsufficiency for genes in the deletion region (or deletion of genes at the breakpoint). 3,4 There are several interesting candidates within the 22q11 deletion involved in dopamine metabolism, mitochondrial function, or microRNA processing. To my knowledge, no single nucleotide variants in any of these candidate genes have been reported in PD cases.…”
mentioning
confidence: 99%